Immunolocalization of DMRTB1 in human testis with normal and impaired spermatogenesis. (28th March 2019) - Hilbold, E.; Bergmann, M.; Fietz, D.; Kliesch, S.; Weidner, W.; Langeheine, M.; Rode, K.; Brehm, R.
Abstract: Background: The transcription factor DMRTB1 plays a pivotal role in coordinating the transition between mitosis and meiosis in murine germ cells. No reliable data are available for human testis. Objectives: The present study aims to examine the testicular expression pattern of DMRTB1 in men showing normal and impaired spermatogenesis. Materials and methods: Immunohistochemistry was performed using 54 human testicular biopsy specimens and a commercial rabbit polyclonal anti‐DMRTB1 primary antibody. RT‐PCR complemented immunohistochemistry. To further characterize immunopositive cells and possible co‐localization, the proliferation marker Ki‐67, the tumor marker PLAP, and an anti‐DMRT1 antibody were used. Results: In men with normal spermatogenesis, a strong immunoreactivity was detectable in a subset of spermatogonia (38.34 ± 2.14%). Some spermatocytes showed a weak immunostaining. Adjacent Sertoli cells were immunonegative. Compared with a hematoxylin and eosin overview staining, these immunopositive cells were almost exclusively identified as Apale and B spermatogonia and primary spermatocytes in (pre‐)leptotene, zygotene, and pachytene stages. In patients with spermatogenic arrest at spermatogonial level, an altered staining pattern was found. No immunoreactivity was detected in Sertoli cells in Sertoli cell‐only syndrome. In germ cell neoplasia in situ (GCNIS) tubules, except for a few (0.4 ± 0.03%), pre‐invasive tumor cells were immunonegative. Seminoma cells showed no immunostaining. Discussion: According to previous findings in mice, it seems reasonable that DMRTB1 is expressed in these normal germ cell populations. Moreover, altered staining pattern in spermatogenic arrest at spermatogonial stage suggests a correlation with mitosis and transformation into B spermatogonia. The absence of DMRTB1 in GCNIS cells and tumor cells might be associated with uncontrolled neoplastic cell proliferation and progression into invasive germ cell tumors. Further research is required to elucidate, for example, the role of DMRTB1 in the malignant transformation of human germ cells. Conclusion: Our data indicate a relevant role for DMRTB1 regarding the entry of spermatogonia into meiosis in men.